Would ending shark meat consumption in Australia contribute to the conservation of white sharks in South Africa?. (October 2020) - Braccini, Matias; Blay, Nick; Harry, Alastair; Newman, Stephen J.
Abstract: South African white sharks have disappeared from one of the world's aggregation 'hot spots'. This has led to speculation that unsustainable fishing of smaller shark species may have displaced white sharks by removing their primary food source. Most of the catch from these fisheries is exported to Australia to supply the domestic 'fish and chips' market so a link has been made between the disappearance of South Africa's white sharks and shark consumption in Australia. As cooked seafood is not properly labelled in Australia, consumers cannot readily distinguish between sustainable and non-sustainable seafood. Hence, a highly promoted campaign was recently initiated to encourage Australians to stop eating 'fish and chips' and as such save South Africa's white sharks. However, most of the consumed shark in Australia is sourced from sustainable domestic fisheries and encouraging Australian consumers to stop eating 'fish and chips' would not help South African white sharks as it would simply displace the issue. It would not address any South African sustainability concerns and would negatively impact a legitimate and sustainable Australian industry. Instead, we encourage the South African government to establish and enforce a governance system for sustainably managing sharks and the Australian government to legislate and enforce the accurate labelling of all types of seafood. Highlights: Speculation links white shark disappearance and unsustainable fishing in South Africa to exports and shark consumption in Australia. Australia consumers find it hard to distinguish between sustainable and non-sustainable seafood. Cessation of fish and chips consumption in Australia would not help South African white sharks. A governance system for sustainably managing sharks is required in South Africa. There is a need for the Australian government to legislate and enforce the accurate labelling of all types of seafood.